Eugène Fromentin, un artiste complet ? - Gubińska, Maria (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2019)
Eugène Fromentin belongs to those outstanding artists who achieved successes in both painting and literature. In his epoch, he was greatly successful thanks to his paintings depicting Algerian nature and customs of that country. A talented writer, fascinated with orientalism, he travelled to Algeria and Egypt in order to search for invigorating impulses for his own imagination, to exploit them artistically and imaginatively as a vast space of sundry possibilities. From his travels to the East, Fromentin brought with him paintings being expressions of his solitary disposition and ‘supplemented’ his painting achievements in his unique way by publishing three travel diaries, A Summer in the Sahara (1857), A Year in Sahel (1859) and Notes from the Journey to Egypt (1881). In the preface to his second travel book he wrote that the objective of his ‘orientalising’ writing was not to restate the painting impressions but to express those feelings that only words can express. In our paper we want to show Fromentin as a painter, writer, traveller, art critic, a man of many talents, undeservedly forgotten, for whom painting was an impulse for creating multidimensional works.